Serological prevalence of the Schmallenberg virus in domestic and wild hosts worldwide: a systematic review and meta-analysis - Dagnaw, Melkie; Solomon, Atsede; Dagnew, Binyam (Frontiers in Veterinary Science, 2024)
The overall serological investigation of SBV is needed to improve modeling predictions and assess the overall impact in ruminant animals which helps to design an intervention to control and prevention strategies.Wild animals are the reservoir for many infectious diseases that bear the constant risk of re-introduction into the human or livestock population. Thus, this study aimed to estimate the overall serological assay of SBV in both domestic and wild ruminants. This systematic review was conducted per Preferred Reporting Items for Systematic Reviews and Meta-Analyses.International databases were employed to search relevant articles. The pooled prevalence with a 95% confidence interval was calculated with a random effects model. The Cochran's Q test, τ 2, and I 2 were used to assess the sources of heterogeneity. In the current meta-analysis, a total of 341 articles were included. The overall pooled proportion of SBV in domestic and wild ruminants was 49.5% and 26%, respectively. Substantial heterogeneity was observed in (I 2 = 99.76%). studies in domestic ruminants and (I 2 = 97.9%; P<0.01) studies in wild ruminants. The pooled prevalence of SBV was significantly associated with publication time, detection techniques, and species of animals. According to subgroup analysis, The highest pooled prevalence of SBV was reported in cattle (5968%), followed by Sheep (3742%) and Goat (18%). In addition sub analysis based on publication year, The pooled prevalence of SBV infection was higher has become endemic after 2013 (4955%) among domestic animals in the world. Of the diagnostic tests used the highest ani-SBV antibodies (66%) were detected by virus neutralizing test. In this Meta-analysis, the major wild animals which infected by SBV were red deer, roe deer, fallow deer, mouflon, and wild boar. The highest sub-pooled prevalence of SBV (46%) was found in roe deer, followed by fallow deer (30%), red deer (27%), mouflon (22%), and wild boar (11%). In general, the prevalence of SBV was high in cattle among domestic ruminants while in roe deer among wild animals. According to the current information provided by this Meta-analysis, evidence-based risk management measures should be established to restrict SBV spread in both domestic and wild ruminants.